2023
DOI: 10.3390/jcm12030944
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bidirectional Relationships between Mental Illness and Rheumatoid Arthritis: A Two-Sample Mendelian Randomization Study

Abstract: A correlation between mental illness and systemic rheumatoid arthritis (RA) has been observed in several prior investigations. However, little is known about the causative relationship between them. The present study aimed to systematically investigate the potential association between genetically determined mental illness and RA. Two-sample bidirectional Mendelian randomization (MR) analysis was performed using publicly released genome-wide association studies (GWAS). We selected independent genetic variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Previous MR research suggested a causal relationship between bipolar disorder and rheumatoid arthritis (RA), with bipolar disorder acting as a protective factor for RA (Xiang et al., 2023). However, no causal association between bipolar disorder and OA has been reported, making our study a pioneering effort to bridge this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous MR research suggested a causal relationship between bipolar disorder and rheumatoid arthritis (RA), with bipolar disorder acting as a protective factor for RA (Xiang et al., 2023). However, no causal association between bipolar disorder and OA has been reported, making our study a pioneering effort to bridge this knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…acting as a protective factor for RA (Xiang et al, 2023). However, no causal association between bipolar disorder and OA has been reported, making our study a pioneering effort to bridge this knowledge gap.…”
Section: F I G U R Ementioning
confidence: 94%
“…This study aims to examine how DAS 28 scores and adherence to treatment correlate with depression and anxiety in patients with rheumatoid arthritis (RA). It investigates the impact of psychological factors on treatment compliance, emphasizing the importance of integrating mental health care in RA management to enhance overall patient outcomes and quality of life (14)(15)(16). The research advocates for a comprehensive approach that addresses both the physical symptoms and psychological well-being of RA patients.…”
Section: Introductionmentioning
confidence: 99%